Implementing Deeper Learning and 21st Century Education Reforms Building an Education Renaissance After a Global Pandemic - Reimers, Fernando M. (Springer International Publishing : Imprint: Springer, 2021)
This open access book is a comparative analysis of recent large scale education reforms that broadened curriculum goals to better prepare students for the 21st century. The book examines what governments actually do when they broaden curriculum goals, with attention to the details of implementation. To this end, the book examines system level reforms in six countries at various levels of development. The study includes system level reforms in jurisdictions where students achieve high levels in international assessments of basic literacies, such as Singapore and Ontario, Canada, as well as in nations where students achieve much lower levels, such as Kenya, Mexico, Punjab-Pakistan and Zimbabwe. The chapters examine system-level reforms that focus on strengthening the capacity to teach the basics, as in Ontario and Pakistan, as well as reforms that aim at building the capacity to teach a much broader set of competencies and skills, such as Kenya, Mexico, Singapore and Zimbabwe. The volume includes systems at very different levels of spending per student and reforms at various points in the cycle of policy implementation, some just starting, some struggling to survive a governmental transition, and others that have been in place for an extended period of time. From the comparative study of these reforms, we aim to provide an understanding of how to build the capacity of education systems to teach 21st century skills at scale in diverse settings.